Metabolic differences in women with premature ovarian insufficiency: a systematic review and meta-analysis - Wang-Yu Cai; Xi Luo; Wei Wu; Jianyuan Song; Ning-Ning Xie; Cuicui Duan; Xiao-Ke Wu; Jian Xu (BMC, 2022)
Abstract Objective This review aimed to investigate the metabolic profile of women with premature ovarian insufficiency (POI) compared relative to women with normal ovarian functioning. Methods A systematic search of PubMed, EMBASE, and the Web of Science for observational studies published up until the 6th of July 2021 that compared the metabolic profile of POI women with a healthy control group were assessed. Mean differences (MD) and 95% confidence interval (CI) were pooled using the fixed or random effect models. Results A total of 21 studies involving 1573 women with POI and 1762 control women were included. POI patients presented significantly higher waist circumference, total cholesterol, low-density lipoprotein, high-density lipoprotein, triglycerides, and fasting glucose. Additionally, POI patients had marginally higher insulin level. However, the differences in systolic, and diastolic blood pressure were non-significant relative to the control group. Conclusions POI is associated with alterations in certain metabolic parameters compared to control women. This finding highlights the importance of early screening and the lifelong management of metabolic health for women with POI.